Komunikasi Budaya Digital Pada Instagram @siberkreasi Untuk Mengetahui Kualitas Literasi Digital - Ibad, Nashoihul; Dewantara, Muhammad Iqbal (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
This research departs from the urgency of digital literacy in the millennial era, especially through the social media platform that is most widely used by this generation, namely Instagram. As one of the pioneers of digital literacy in Indonesia, @siberkreasi account is the main choice in disseminating information and digital education to the public. This research aims to analyze how @siberkreasi accounts are able to play a role in educating the nation's life through digital literacy, especially among the younger generation, with a focus on students. This study uses a qualitative method with a postpositivism approach, which prioritizes subjective and interpretive understanding of the phenomenon being studied. The data was collected through in-depth interviews with founders and content creators from @siberkreasi accounts. The results of the study show that the @siberkreasi account is a non-profit account that consistently supports the development of digital literacy among the younger generation. In its content creation, this account focuses more on a constructivist approach, which the founder believes is an important method to effectively improve digital literacy. These findings emphasize the importance of an educational and constructive approach in an effort to improve digital literacy in Indonesia, especially through social media which is popular among millennials.   Keywords: Digital literacy, Instagram @siberkreasi